2019
DOI: 10.1002/aelm.201800648
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Coated Silk Fabrics with Conductive Property for Wearable Electronic Textiles Application

Abstract: The desire for this lightweight and flexible electronics has grown increasingly, and the flexible and wearable electronic textiles can be realized by coating traditional textiles with conductive materials. Here, the conductive silk fabrics are prepared by coating graphene oxide (GO) onto silk fabrics and followed by thermal reduction. The scanning electron microscope results show that the GO coated onto silk fabrics successfully forms a continuous thin film. The oxygen functional groups are removed by thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 48 publications
(47 reference statements)
1
39
0
Order By: Relevance
“…Although in some points, weight loss of RGO‐coated samples was higher than pure cotton owing to the pyrolysis of oxygen from the remaining oxygen‐bearing functional groups in the coupling agent and RGO. [ 44 ] However, higher decomposition temperature (in each stage), lower weight loss throughout the analysis period, and more residue suggest that the thermal stability and a heat resistance of NPs incorporated samples (especially Cu) is higher [ 16 ] than the pure silk and other RGO‐coated samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in some points, weight loss of RGO‐coated samples was higher than pure cotton owing to the pyrolysis of oxygen from the remaining oxygen‐bearing functional groups in the coupling agent and RGO. [ 44 ] However, higher decomposition temperature (in each stage), lower weight loss throughout the analysis period, and more residue suggest that the thermal stability and a heat resistance of NPs incorporated samples (especially Cu) is higher [ 16 ] than the pure silk and other RGO‐coated samples.…”
Section: Resultsmentioning
confidence: 99%
“…Coupling or crosslinking agents can enhance GO interaction and bonding strength between GO and fabrics. [ 8,9 ] In this study, we used biocompatible 3‐glycidyloxypropyl trimethoxy silane as a coupling agent to increase the bonding durability and reaction sites between silk fabric and GO. The hydrolyzed 3‐glycidyloxypropyl trimethoxy silane produces hydroxyl groups, which act as the binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BSA and RSF protein were also found to be used as adhesive in silk/graphene composites. Zulan et al reported highly conductive silk fabric, which was wrapped with GO by dipping into GO solution followed by thermal reduction, where BSA and RSF protein was used as adhesive . Flame retardant property can also be improved significantly after several cycles of coating‐reduction process 158a,159.…”
Section: Graphene Modified Textile Composites In Relevant To the Propmentioning
confidence: 99%